Authenticity Within Oatly’s Reaction to the Communication Crisis - Atika Rusy Kuncoro (Jurnal Audience: Jurnal Ilmu Komunikasi, 2022)
In exploring how people make sense of Oatly’s crisis reaction and its authenticity, this study employed qualitative research analysis. Engaged to symbolic interaction theory, situational crisis communication theory and authenticity, data from interviews with Oatly consumers were investigated to collect pattern and meaning to further extract the key themes. Taken place in Oatly original base in Sweden, this research argues that the way consumer see authenticity in a brand’s action is based on their own preferred concept. Three themes regarding how consumer make sense of Oatly’s reaction to the crisis were concluded. Moreover, three themes emerged during analysis regarding to how consumer understand authenticity in a crisis response.